Challenges and Opportunities of Managing Social Media Generated Records in Institutions of Learning: A Case of the Midlands State University, Zimbabwe - Pondiwa, Shephard; Phiri, Margaret (Springer New York LLC, 2021)
The management of institutions of learning largely depends on the way their records are managed. Social media use and management of records created on social media is a subject that has raised a number of issues that require academic research to focus on. It has become inevitable for organizations and institutions of learning to embrace the use of several social media platforms in their conduct of business. The paper explores how the Midlands State University (MSU) in Zimbabwe has embraced the use of social media in the conduct of official business and how this has affected teaching and learning. The study employed a case study approach that used questionnaires and semi structured and structured interview questions. This research views social media generated records as records which must be managed well as they are part and parcel of the institution’s assets and that if they are not properly managed this affects the provision of education. The paper is informed by the continuum concept. The objectives of the study were to identify the social media platforms used at the Midlands State University, challenges and opportunities brought in by social media as a learning platform as well as a communication platform. The study also aimed to develop a model that can be used to integrate social media generated records into the main records management system since such integration is key to the proper management of institutions of higher learning.